Politeness Strategies Used by The Main Characters in Mulan Movie 2020 - Angelia Secilia Sitinjak; Immanuel Prasetya Gintings (Universitas Negeri Medan, 2023)
This study aims to examine the kinds of politeness strategy uttered by the main characters in Mulan (2020) and the different politeness strategies used by the main characters to the others characters within the movie. Qualitative textual analysis methods were applied in collecting the data of this study. The data were obtained from the script and movie Mulan (2020). Furthermore, the data were classified based on their types of politeness and also based on the different politeness used by the main characters. This study was conducted using Brown and Levinson (1987) theory. The analysis revealed that the main characters in the movie Mulan applied four strategies proposed by Brown and Levinson with the total of bald on record (9), positive politeness (14), negative strategies (6) and off record (2). Regarding to the types of politeness, Mulan as the main character consistently tends to use positive politeness strategies in her utterances throughout the movie. The different politeness strategies used by the main characters to the other characters is Mulan often use bald on record and positive politeness strategy when she talks to her family. When she talks to her friends and neighbor, Mulan often use positive politeness strategy. The last is when Mulan talks to the emperor, she used negative politeness strategy.